2010
DOI: 10.1016/j.jvs.2010.05.065
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral internal carotid and vertebral artery dissection after a horse-riding injury

Abstract: Blunt cerebrovascular injuries, defined as blunt injuries to the internal carotid or vertebral arteries, are uncommon and usually occur in victims of high-speed deceleration motor vehicle crashes. A blunt cerebrovascular injury after an equestrian accident is an extremely unusual presentation. In recent years, advances in screening and treatment with pharmacologic anticoagulation before the onset of neurologic symptoms have improved outcomes for these patients. Endovascular stenting and embolization, although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“… [11] In VAI, treatment options are anticoagulants, antiplatelets, thrombolysis, endovascular or surgical treatment. 12 , 13 , 14 In our case, VAI was excluded by the lack of thrombus or dissection of the vertebral artery from CT angiography, which was ordered upon the presence of the stable C1 lamina fracture (one of the risk factors) and worsening findings upon neurological examination. This data suggests that the acute ischemic lesion in the left parieto-temporo-occipital region detected in the diffusion MRI of our patient may have not been developed due to VAI, but may have developed due to hypoperfusion leading to loss of consciousness.…”
Section: Discussionmentioning
confidence: 92%
“… [11] In VAI, treatment options are anticoagulants, antiplatelets, thrombolysis, endovascular or surgical treatment. 12 , 13 , 14 In our case, VAI was excluded by the lack of thrombus or dissection of the vertebral artery from CT angiography, which was ordered upon the presence of the stable C1 lamina fracture (one of the risk factors) and worsening findings upon neurological examination. This data suggests that the acute ischemic lesion in the left parieto-temporo-occipital region detected in the diffusion MRI of our patient may have not been developed due to VAI, but may have developed due to hypoperfusion leading to loss of consciousness.…”
Section: Discussionmentioning
confidence: 92%
“…At our institution, CT of the cervical spine with contrast is routinely obtained for all trauma patients with a significant mechanism, which is how her injury came to be found. Multiple studies and review have found that CTA is an effective screening tool if it is equal to or greater than 8-slice multidetector array, with a sensitivity of 100% for carotid injury and 96% for vertebral injury [ 13 , 15 ]. Ultrasound was found to be ineffective with a sensitivity of 38% [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Traumatic CCF is usually accompanied by significant cervical damage and additional damage to the vasculature, including lesions of the vertebral arteries. [4][5][6] Additionally, the cavernous sinuses are closely associated with numerous structures related to ocular function, including the superior and inferior ophthalmic veins as well as cranial nerves III, IV, V 1 , V 2 , and VI. 1 The abducens nerve is particularly vulnerable to injury from vascular engorgement and trauma due to its proximity to the internal carotid artery and unsecured course through the cavernous sinus.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] CCF is usually treated aggressively with a variety of neurosurgical or vascular procedures to prevent progression of ophthalmic manifestations and irreversible consequences, such as permanent optic nerve damage, and to counter potential neurologically devastating or even fatal outcomes from blunt cerebrovascular injury, including intracranial hemorrhage and embolic stroke. [1][2][3][4] We describe a case of spontaneous resolution of ophthalmologic sequelae in a patient who developed post-traumatic, bilateral carotid dissections that resulted in bilateral CCF and central retinal venous insufficiency.…”
Section: Introductionmentioning
confidence: 99%